Biological control of Meloidogyne spp. with nematophagous fungi in carrot culture (Research, Society and Development, 2022)
The carrot is a vegetable of the tuberous roots group, cultivated on a large scale in several Brazilian states. Among the phytosanitary problems associated with the crop, galling nematodes of the genus Meloidogyne stand out, whose infestations can lead to up to 100% loss of production. The search for alternatives to chemical control has intensified in recent years with the advent of bionematicides, especially those formulated based on nematophagous fungi. Thus, the aim of this study was to compare the efficiency of the application of the fungi Paecilomyces lilacinus, and Pochonia chlamydosporia compared to the use of chemical control, in carrot planting under root-knot nematode infestation. The study was carried out at Instituto Taquaritinguense de Ensino Superior (ITES), municipality of Taquaritinga, São Paulo state, Brazil under field conditions, using the hybrid carrot var. 'Sirkana'. The experimental design was in complete randomized blocks with five replications and six treatments: 1. P. lilacinus; 2. P. chlamydosporia; 3. P. lilacinus + P. chlamydosporia; 4. Adicarb; 5. Cadusaphos and 6. Check Treatment (not applicable). The doses of the respective treatments consisted of 0.67 L/m2 of planting bed with substrate colonized by nematophagous fungi, 30 kg/ha of p.c. of Aldicarb, and 25 kg/ha of p.c. of Cadusaphos. Based on the results obtained, the nematophagous fungi P. lilacinus and P. chlamydosporia can be recommended for the control of root-knot nematodes in carrot cultivation, as an alternative to chemical control.